Penerapan Teori Diversi Terhadap Kasus Anak Ditinjau Dari Hukum Pidana Islam - Rosmida Wati Siregar; Ihsan Helmi Lubis (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
The problem in this study is the application of diversion at the Padangsidimpuan Police Station in terms of Islamic Criminal Law. The type of research used in this research is field research, using a Juridical Empirical approach, primary data sources are Padangsidimpuan City Police investigators and secondary data sources are books, journals and others. Data collection techniques used consisted of interviews, observation, and documentation. Qualitative descriptive data analysis techniques. The results of this study are the application of diversion efforts at the Padangsidimpuan City Police has not been fully implemented in accordance with Law Number 11 of 2012 concerning the Juvenile Criminal Justice System by taking into account the best interests of children (victims and suspects), the parties invited for diversion include: victims and family, suspect and family, BAPAS, Bapemas, institutions or social organizations accompanying children. Islamic Criminal Law Review In Islah, criminal acts that cannot be pursued are criminal acts that fall into the Hudud category such as adultery, accusing adultery, alcohol, apostasy and rebellion. Apart from these categories, peaceful means can be taken even if it involves serious crimes such as murder and so on. While in diversion, the benchmark is the period of confinement. Peace efforts can be pursued while threatened with imprisonment under 7 years and not a recidivist.